Caring for a child with severe intellectual disability in China: The example of Rett syndrome - Lim, Faye; Downs, Jennepher; Li, Jianghong; Bao, Xinhua; Leonard, Helen (Informa Healthcare, 2013)
Purpose: Rett syndrome is one of several genetic disorders known to cause severe intellectual and physical disability, mostly in girls. Girls affected by Rett syndrome appear to develop normally in the first 6 months of life, after which the usual clinical presentation comprises regression of communication and hand skills, the appearance of hand stereotypies and impaired gait. Intellectual disability affects more than 1.5% of the population of children in developing countries yet we know little about the daily lives and support services available for them and their caregivers. Method: This qualitative study explored the daily experiences of 14 mothers and one grandmother caring for a child with Rett syndrome in China via telephone interviews. Results: Participants reported a lack of education, rehabilitation and support services available to them. Limited access to information reduced families’ capacity to adequately meet the needs of their child. These gaps were further exacerbated by discrimination and perceived stigma from some members of the community. Conclusions: Additional support services and educational programs at the governmental level can improve the quality of life of persons with an intellectual disability and their families and programs involving community participation in the care of people with disabilities may help to address discrimination.